Hubungan Konsep Diri dan Dukungan Sosial dengan Psychological Well-Being pada Mahasiswa Semester Akhir - Satya Ananda Ratmo; Sahat Saragih; Yanto Prasetyo (JIWA: Jurnal Psikologi Indonesia, 2025)
AbstractFinal semester students transitioning from education to the workforce face various challenging aspects of life, leading to high levels of stress that negatively impact their psychological well-being. Psychological well-being is understood as a condition in which individuals are free from psychological pressure. The aim of this research is to examine whether there is a relationship between self-concept and social support with psychological well-being among final semester students, both partially and simultaneously. The study population consists of final semester students from the psychology faculty at Universitas 17 Agustus 1945 Surabaya, with a total of 312 respondents. The approach used is a correlational quantitative approach employing three measurement tools: Ryff’s Psychological Well-Being Scale, Self Concept Scale, and The Multidimensional Scale of Perceived Social Support. The results of the study indicate a significant relationship between self-concept and social support with psychological well-being among final semester students. Specifically, the self-concept variable shows a significant positive relationship with psychological well-being, while the social support variable also exhibits a significant positive relationship with psychological well-being.Keywords: social support, self-adjustment, psychological well-being, final semester students.AbstrakMahasiswa semester akhir yang mengalami transisi dari dunia pendidikan ke dunia pekerjaan melalui berbagai aspek kehidupan yang menantang mengalami tingkat stres tinggi yang berdampak negatif pada psychological well-beingnya. Psychological well-being dimaknai sebagai kondisi dimana individu terbebas dari tekanan psikologis. Tujuan penelitian ini untuk menguji apakah ada hubungan antara konsep diri dan dukungan sosial dengan psychological well- being pada mahasiswa semester akhir, baik secara parsial maupun secara simultan. Populasi penelitian adalah mahasiswa semester akhir fakultas psikologi di Universitas 17 Agustus 1945 Surabaya, dengan jumlah responden penelitian sebanyak 312 mahasiswa. Pendekatan yang digunakan yaitu pendekatan kuantitatif korelasional dengan menggunakan 3 (tiga) alat ukur, yaitu Ryff’s Psychological Well-Being Scale, Self Concept Scale, dan The Multidimensional Scale of Perceived Social Support Scale. Hasil penelitian secara simultan menunjukkan adanya hubungan yang signifikan variabel konsep diri dan dukungan sosial dengan psychological well-being pada mahasiswa akhir. Secara parsial variabel konsep diri dengan psychological well-being menunjukkan hasil yang signifikan dengan arah yang positif dan variabel dukungan sosial dengan psychological well-being menunjukkan hasil yang signifikan dengan arah yang positif.Kata kunci: dukungan social, Konsep diri, psychological well-being, mahasiswa baru.